2023
DOI: 10.3390/pathogens12060766
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Perspectives for Microbiota Transplantation in Digestive Diseases and Neoplasia—A Literature Review

Adrian Boicean,
Dan Bratu,
Ciprian Bacila
et al.

Abstract: In a mutually beneficial connection with its host, the gut microbiota affects the host’s nutrition, immunity, and metabolism. An increasing number of studies have shown links between certain types of disease and gut dysbiosis or specific microorganisms. Fecal microbiota transplantation (FMT) is strongly advised for the treatment of recurrent or resistant Clostridium difficile infection (CDI) due to its outstanding clinical effectiveness against CDI. The therapeutic potential of FMT for other disorders, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Molecular examinations unveiled the presence of only two out of the three studied viral genes in each autopsy specimen, and immunohistochemical analysis confirmed the occurrence of viral nucleocapsid in a diminished proportion within the lungs. Another frequent complication of SARS-CoV-2 infection that can cause severe multiorgan damage and death is Clostridium Difficile enterocolitis, but recent treatments can decrease the mortality rate, mainly through fecal microbiota transplantation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular examinations unveiled the presence of only two out of the three studied viral genes in each autopsy specimen, and immunohistochemical analysis confirmed the occurrence of viral nucleocapsid in a diminished proportion within the lungs. Another frequent complication of SARS-CoV-2 infection that can cause severe multiorgan damage and death is Clostridium Difficile enterocolitis, but recent treatments can decrease the mortality rate, mainly through fecal microbiota transplantation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed that genetic variations in genes associated with the interleukin (IL)-23/IL-17 axis can impact the digestive mucosal integrity through their influence on the differentiation of Th17 cells, with implications in both diseases [ 16 ]. IL-17 and IL-22 play a crucial role in modulating the function of Th17 cells.…”
Section: Immunological Interplay: Unraveling the Connection Between T...mentioning
confidence: 99%
“…Other studies that describe the similarities between CD and ITB highlight the impact of gene polymorphisms within the IL-23/IL-17 axis on susceptibility to IBD and the development of ITB. In the same vein, genome-wide association studies conducted on Japanese and Korean populations have revealed associations between various genes that are signaling this pathway, which can predispose individuals to the development of IBD or, in the case of TB infection, to the development of ITB [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Previous studies involving population from China have noted that genetic polymorphism, specifically a single-nucleotide polymorphism in IL22 rs2227473, was found to be significantly correlated with susceptibility to developing TB [ 16 , 33 ].…”
Section: Immunological Interplay: Unraveling the Connection Between T...mentioning
confidence: 99%
See 2 more Smart Citations